Answer: Both A, and C
Step-by-step explanation:
The answer to the first system of equations (2x+2y=16) would be
x=3 and y=5 ( 3x-y=4 )
Which means we have to find out which of the other equations has an x value of 3, and a y value of 5.
If A is 2x+2y=16, then x=3 and y=5
6x-2y=8
If B is x+y=16, then x=5 and y=11
3x-y=4
If C is 2x+2y=16, then x=3 and y=5
6x-2y=8
If D is 6x+6y=48 , then x=-2 and y=10
6x+2y=8
Both A and C are equal to the first system of equations, which means they are both correct answers.
When we simplify (3 + √5)(3 + √2), the result obtained is:
9 + 3√2 + 3√5 + √10
<h3>Surd operation </h3>
a√b × c√d = (a × c)√(b × d)
<h3>How to simplify (3 + √5)(3 + √2)</h3>
(3 + √5)(3 + √2)
Expand by clearing the bracket
3(3 + √2) + √5(3 + √2)
9 + 3√2 + 3√5 + √10
Thus,
(3 + √5)(3 + √2) = 9 + 3√2 + 3√5 + √10
Learn more about surd:
brainly.com/question/24700530
#SPJ1
Answer: There are 10 sides
---------------------------------------------
x = measure of each interior angle
y = measure of each exterior angle
We know that x = 4y as "each interior angle is four times the measure of each exterior angle"
The interior and exterior adjacent angles are supplementary
x+y = 180
4y+y = 180
5y = 180
5y/5 = 180/5
y = 36
If y = 36, then
n = 360/y
n = 360/36
n = 10
Answer:
3x + y = -16
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given a system of equations are
5x+6y =-5
- 2x - 5y = -11
multiply '1' and Adding two system of equtions
+ 1 (5x + 6y = -5)
+ 1 (<u> -2x - 5y = -11)</u>
<u> 3x + y = -16 </u>
<u>Final answer:-</u>
5x + 6y = -5
<u> -2x - 5y = -11</u>
<u> 3x + y = -16 </u>
<u />
Answer:
6^-9
Step-by-step explanation:
(6 ^10 × 6 ^− 4 ) (6 ^− 5 × 6 ^2 ) (6 ^10 × 6 ^− 4 ) (6 ^− 5 × 6 ^2 )as a single term of the form 6 ^n.
hope this helped <3